2022
DOI: 10.3390/tomography8010036
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Eye Dose for Physicians in CT Fluoroscopy-Guided Biopsy

Abstract: It is important to evaluate the radiation eye dose (3 mm dose equivalent, Hp (3)) received by physicians during computed tomography fluoroscopy (CTF)-guided biopsy, as physicians are close to the source of scattered radiation. In this study, we measured the radiation eye dose in Hp (3) received by one physician during CTF in a timeframe of 18 months using a direct eye dosimeter, the DOSIRISTM. The physician placed eye dosimeters above and under their lead (Pb) eyeglasses. We recorded the occupational radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Dosimeters placed in the vicinity of the lens, such as the Eye-D and DOSIRIS, can also be used [ 26 , 48 , 49 , 50 , 51 , 52 ]; the passive DOSIRIS dosimeter, which does not provide real-time monitoring, was designed to measure the lens dose, but the real-time i3 system may be more effective for reducing occupational doses. The use of dosimeters such as the i3 will be valuable in situations such as IVR, in which exposure doses are high and instantaneous monitoring is required [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dosimeters placed in the vicinity of the lens, such as the Eye-D and DOSIRIS, can also be used [ 26 , 48 , 49 , 50 , 51 , 52 ]; the passive DOSIRIS dosimeter, which does not provide real-time monitoring, was designed to measure the lens dose, but the real-time i3 system may be more effective for reducing occupational doses. The use of dosimeters such as the i3 will be valuable in situations such as IVR, in which exposure doses are high and instantaneous monitoring is required [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main concern of CT guidance is the radiation dose to the interventional radiologist and the patients [ 70 ] even if some studies reported values in line with recommended dose limits for occupational radiation exposure [ 71 ]. To reduce the time needed for placing the probe/needle and therefore the radiation dose, some navigation systems have been developed to assist lung biopsies and thermal ablation therapies, and studies demonstrated that CT assisted with stereotactic navigation reduces the time for ablation probe placement, the number of needle adjustments, skin punctures, and fluoroscopy time [ 72 , 73 ].…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Fluoroscopy guided interventional procedure is associated with the risk of radiation exposure to patients and medical staff [1][2][3][4][5][6][7][8][9]. Therefore, it is important to optimise radiation protection for patients and medical staff [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Endoscopic retrograde cholangiopancreatography (ERCP) is an essential procedure in the diagnosis and treatment of hepatobiliary diseases, but with the development of treatment devices and techniques, increased radiation exposure to patients and medical staff is a critical issue [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%